1997
DOI: 10.1046/j.1365-2958.1997.2101576.x
|View full text |Cite
|
Sign up to set email alerts
|

An RNA polymerase α subunit mutant impairs N‐dependent transcriptional antiterminationin Escherichia coli

Abstract: SummaryWe show that the rpoA341 mutation in the gene encoding the ␣ subunit of Escherichia coli RNA polymerase results in a decreased level of transcripts originating from the lytic promoters p L and p R of infecting phage. However, using lacZ fusions we demonstrate that initiation of transcription from both p L and p R is not impaired in the rpoA341 host. Rather, it is the level of the longer, antiterminated p L -and p R -derived transcripts which is altered: the activity of ␤-galactosidase in bacteria harbou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
1
20
1
Order By: Relevance
“…1) or both λ plasmid and a plasmid overexpressing the N gene. As a control strain, we used the rpoA341 mutant, which was previously shown to be defective in N-dependent anti-termination (Obuchowski et al 1997). As expected, we did not observe any significant effect of the provision of the N protein in this mutant (Table 4).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…1) or both λ plasmid and a plasmid overexpressing the N gene. As a control strain, we used the rpoA341 mutant, which was previously shown to be defective in N-dependent anti-termination (Obuchowski et al 1997). As expected, we did not observe any significant effect of the provision of the N protein in this mutant (Table 4).…”
Section: Resultssupporting
confidence: 52%
“…The single copy p R -lacZ and p L -lacZ fusions have been described previously (Obuchowski et al 1997).…”
Section: Methodsmentioning
confidence: 99%
“…RNA polymerase mutations in b [19][20][21][22] and a subunits, [23][24][25] defective in supporting the growth of l phage as well as impaired for N-mediated antitermination, have been reported. Here, we describe the isolation and characterization of RNAP mutants near the upstream edge of an RNA:DNA hybrid and at the beginning of the RNA-exit channel of the EC that are defective specifically for transcription antitermination mediated by the N protein of a lambdoid phage, H-19B.…”
Section: Discussionmentioning
confidence: 98%
“…11,12 N interacts with nut RNA through its N-terminal ARM sequences and with the EC through its C-terminal domain. 18 Although RNAP mutants defective in l phage growth have been reported, [19][20][21][22][23][24][25] the interacting surface on the EC for N has remained elusive, as has the mechanism by which N imparts the antitermination property to RNAP.…”
Section: Introductionmentioning
confidence: 99%
“…6). Despite impaired N-dependent antitermination (Obuchowski et al 1997c) phage k lytic development is normal in the rpoA341 mutant (Szalewska-Palasz et al 1996); we therefore decided to use this strain as a host in experiments on the k lytic development in cells that overproduce CII and CIII at 30°C. We found that overexpression of cII and cIII causes a dramatic inhibition of phage kcIb2 lytic growth (Fig.…”
Section: Inhibition Of Phage K Lytic Development By Overproduction Ofmentioning
confidence: 99%